Форми господарювання на землі: методологічний аспект - Збарський, В. К.; Кальченко, Сергій Володимирович; Кальченко, Сергей Владимирович; Kalchenko, Serhii (My University, 2016)
UK: У статті проаналізовано теоретичні та методологічні засади оцінки ефективності співпраці різних суб’єктів аграрного виробництва за умов забезпечення їх конкурентоспроможності, обґрунтовано засади раціонального поєднання діяльності суб’єктів аграрного виробництва в умовах багатоукладної економіки, а також необхідність оптимізації наявного методичного забезпечення. EN: The article analyzes the theoretical and methodological principles of assessing the effectiveness of cooperation between various agricultural production under conditions ensuring their competitiveness. The necessity of optimization of existing methodologies. The authors identify the following methodological aspects of optimization. The first question is the choice of methodology called signs or indicators, which may be described or defined size companies and was built to scale for comparison. The second methodological issues - concerns the list of factors that influence the size of the company. The third question of methodology - the choice of evaluation indicators based on the criteria of effectiveness and efficiency of the company, depending on its size and taking into account the impact of a combination of factors. The fourth methodological issues - establishment of dependency or development of methods of assessment between size indicator and a numeric value indicator, which characterizes the size of the company. The fifth issue is caused methodology novelty of the task - it is not about the size of a single enterprise, and ratio of the number of enterprises. For an objective evaluation of different forms of management and administration should be provided with the necessary diversity of forms themselves or a wide range, which may appear to substantial differences and equal starting conditions for each form or legal balance in the position holders. The article emphasizes the need to allow a consistent orientation to market relations for guarantees product competitiveness of all companies - small, medium and large, as well as quality of life, development of social infrastructure in rural areas, keep it as the basis of life and employment.
Forms of business on earth: methodological aspects
Keywords: відносини власності; конкурентоспроможність; малі форми аграрного виробництва; сільські території; ресурсний потенціал; competitiveness; small forms of agriculture; rural areas